Penguatan Kapasitas SDM Pemandu Wisata Geopark pada Pokdarwis KWIK Berkah Mandiri Desa Wisata Adiluhur dalam Mendukung Kabupaten Kebumen Menjadi Unesco Global Geopark 2024 - Izaz Rakha Anggara; Novanda Alim Setya Nugraha; Satya Helfi Agustianto; Fatimah Az Zahra; Siti Rhofiah; Salsabila Septi Sukmayanti; Isnaeni Fatmawati; Anisa Febriana; Arian Ardiansyah; Gilang Riyanto; Rezky Arkan Syarif Pohan; Dio Syahputra; Mutia Dian Safitri; Khansaa Adhelia Kurnia; Safitri Muhammad Wildan Rusli; Elang Muhammad Rangga Aryadifa; Wuwuh Andayani (jurnal ABDIMAS Indonesia, 2024)
This paper assesses the capacity-building program for tour guides in Pokdarwis KWIK Berkah Mandiri at Adiluhur Tourism Village, aimed at supporting Kebumen Regency’s bid for UNESCO Global Geopark status by 2024. The program utilizes a participatory approach with intensive training and workshops to enhance knowledge, communication skills, and storytelling related to local geological and cultural heritage. English language training is also included to improve interactions with international tourists. Featured on Asterdewi.id, the new "Go English Geopark" program contributes to better service quality, enhanced tourist experiences, and increased local engagement in geopark promotion and conservation. The program plays a significant role in Kebumen’s goal of achieving UNESCO Global Geopark status.